Development of intelligent air-conditioning system - Shafie, Amir Akramin; Khan, Md. Raisuddin; Al-haieaid , H.; Ebrahim, M. (2006)
This paper presents an air-conditioning system that regulates room temperature via the use of multiple-sensor system that is named as “Intelligent Air-Conditioning System”. Airconditioning system has become one of most important human comfort technologies especially for countries near the equator. Conventional methods of regulating room temperature by air-conditioning system using single sensor have been integrated into most of today’s split type and window type air-conditioner. The demands from customer now from air condition technology are for more human comfort, energy saving and smart gadgetry thus the trend in research is to incorporate artificial intelligent technology in this field. However, many research in this area concentrate on maximizing the use of a single located near the air intake area of the air-conditioning system. In this paper we present a case for the use of multiple sensors to determine the temperature distribution more accurately throughout the room and creating a system that will provide a higher degree of human comfort with less energy consumed.